2001
DOI: 10.1007/s11661-001-0013-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic deformation behavior of an oxide-dispersed tungsten heavy alloy fabricated by mechanical alloying

Abstract: The objective of this study is to investigate the dynamic deformation and fracture behavior of an oxide-dispersed (OD) tungsten heavy alloy fabricated by mechanical alloying (MA). The tungsten alloy was processed by adding 0.1 wt pct Y 2 O 3 powders during MA, in order to form fine oxides at triple junctions of tungsten particles or at tungsten/matrix interfaces. Dynamic torsion tests were conducted for this alloy, and the test data were compared with those of a conventional liquid-phase sintered (LPS) specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In the present study, grain size control can therefore be attributed to the presence of yttrium oxides in the W-M interface. Similar observations of grain size reduction wherein oxide dispersed alloy has an average tungsten grain size of 15 µ against 27 µ of a base alloy has been reported in 93W-4.9Ni-2.1Fe alloy with 0.1 wt % oxide content 11 . In the present study, as listed in Table 2, average grain size is 32±6µ after LPS and 16±7µ after second swaging.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, grain size control can therefore be attributed to the presence of yttrium oxides in the W-M interface. Similar observations of grain size reduction wherein oxide dispersed alloy has an average tungsten grain size of 15 µ against 27 µ of a base alloy has been reported in 93W-4.9Ni-2.1Fe alloy with 0.1 wt % oxide content 11 . In the present study, as listed in Table 2, average grain size is 32±6µ after LPS and 16±7µ after second swaging.…”
Section: Discussionsupporting
confidence: 83%
“…As demand for higher and better mechanical properties increases in recent years, amorphous and nanocrystalline tungsten alloys have attracted enormous research attention. It has been demonstrated that the mechanical properties of tungsten alloys can be modified and improved by controlling their microstructures through mechanical alloying (MA) [1][2][3][4][5][6][7][8][9][10], alloying with Mo and Re [11], cyclic heat treatment [12,13], surface carburization [14,15], solid-state sintering [16] and oxide dispersion [5,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent the grain growth, lots of research papers focused on adding inhibitors to hinder grain coarsening by changing the energy states of the W grains during sintering. Recent literature has reported that adding trace amount of rare earth elements or their oxides can refine the grain size and enhance the penetration performance of tungsten heavy alloy [12][13][14][15]. Some researchers adopt high-energy ball milling (HEBM) combining with novel sintering technologies, such as two-stage sintering, microwave sintering and electric current activated sintering, to prepare ultrafine grained WHAs or tungsten [2,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%